Epidemiological Trends of Racial Differences in Early- and Late-onset Group B Streptococcus Disease in Tennessee. (8th October 2020) - Hamdan, Lubna; Vandekar, Simon; Spieker, Andrew J; Rahman, Herdi; Ndi, Danielle; Shekarabi, Emily S; Thota, Jyotsna; Rankin, Danielle A; Haddadin, Zaid; Markus, Tiffanie; Aronoff, David M; Schaffner, William; et al.
Abstract: Background: The rates of early-onset group B Streptococcus (GBS) disease (EOGBS) have declined since the implementation of universal screening and intrapartum antibiotic prophylaxis guidelines but late-onset (LOGBS) rates remain unchanged. Racial differences in GBS disease rates have been previously documented, with Black infants having higher rates of EOGBS and LOGBS, but it is not known if these have persisted. Therefore, we sought to determine the differences in EOGBS and LOGBS disease by race over the past decade in Tennessee. Methods: This study used active population-based and laboratory-based surveillance data for invasive GBS disease conducted through Active Bacterial Core surveillance in selected counties across Tennessee. We included infants younger than 90 days and who had invasive GBS disease between 2009 and 2018. Results: A total of 356 GBS cases were included, with 60% having LOGBS. EOGBS and LOGBS had decreasing temporal trends over the study period. Overall, there were no changes in temporal trend noted in the rates of EOGBS and LOGBS among White infants. However, Black infants had significantly decreasing EOGBS and LOGBS temporal trends (relative risk [95% confidence interval], .87 [.79, .96] [ P = .007] and .90 [.84–.97] [ P = .003], respectively). Conclusions: Years after the successful implementation of the universal screening guidelines, our data revealed an overall decrease in LOGBS rates, primarily driven by changes among Black infants. More studies are needed to characterize the racial disparities in GBS rates, and factors driving them. Prevention measures such as vaccination are needed to have a further impact on disease rates. Abstract : Decades after implementation of universal prenatal screening guidelines, late-onset group B Streptococcus disease remains more common than early-onset disease with differences by race noted. Early- and late-onset diseases are significantly decreasing in Black infants while remaining constant among White infants.